Pelatihan Seni Bela Diri Pencak Silat Sebagai Pengembangan Ekstrakurikuler Sekolah Dalam Pembentukan Pendidikan Karakter Bagi Pemuda Desa Sunting Kecamatan Bandar Pusaka Kabupaten Aceh Tamiang - Rahmad; Putri Syahira; Raudhatul Hasanah; Usmaidar (Fusion: Jurnal Pengabdian kepada Masyarakat, 2024)
The implementation of Pencak Silat Tapak Suci martial arts training in Sunting Village, Aceh Tamiang Regency aims to develop youth character values through Pencak Silat martial arts training activities. The method used is a qualitative method that directly describes the character building of youth through Pencak Silat. This training was conducted on 13 March 2024. The results showed that Pencak Silat Tapak Suci had a positive impact on improving character values, especially discipline, among the youth of Sunting Village. Character strengthening is done through opening and closing ceremonies, habituation of values such as discipline, respecting elders, and including God in every activity. The process of instilling character values through this training goes through an introduction and understanding stage, as well as an application stage. Evaluation is conducted to ensure the learning goes well. Supporting factors include willingness to learn, good habituation, and parental support, while inhibiting factors include lack of talent, inadequate facilities and infrastructure, and patience in training.